THE TOXICITY OF THE FISHSOURCE MADE FROM A TETRODOTOXIN-BEARING PUFFER TOQUIGENER GLOERFELTI - Ha, Dao Viet; Sato, Shigeru (Vietnam Journal of Marine Science and Technology, 2014)
The experiment of making fishsource using a TTX-bearing puffer Toquigener gloerfelti as a material was conducted during 12 months in order to observe a trend of toxicity in the fishsource product. The result showed that toxicity had been decreased by time and after 12 months; about 86.43 - 93.93 % of initial toxicity was disappeared. The reason for this is the increasing of pH in the fermentation condition caused the decomposition of some tetrodotoxin moleculars. Notibly, after long time of experiment with high salinity, acidic or neutrolize condition, still certain toxicity (6.07 - 13.57%) was remaining in puffer fishsource product. On the other hand, according to local fishsource producers, fishsource is often ready to be commercial after 3-4 months of proccessing, that may contain 49.44 - 37.47% of initial toxicity (based on the data obtained from this study). It means that if initital toxicity in the fishsource material was high enough, there is a possibility to cause human poisoning. The studied result indicated that using toxic puffer as fishsource material is not safe for human consumption.